Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Penalaran Matematis Dan Kemandirian Belajar Siswa - Karimah, Inayatul; Pratama, Loviga Denny (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to determine the positive and significant effect of PBL model on reasoning ability and independence of learning mathematics of students taught in class VII MTS Miftahul Hasan; determine the magnitude of the influence of PBL model on reasoning ability and independence of learning mathematics of students taught in class VII MTS Miftahul Hasan. From the results of the discussion of this study, the average pretest for the class that used the PBL approach was 59.00, while the control class was 56.83. After being given different learning, the average value of students' posttest became 83.3 for the experimental class (PBL) and 70.1 for the control class (conventional). Based on hypothesis testing, obtained tcount = 6.151 at a significant level = 0.05 and ttable = 2.042. By comparing between thitung and ttabel, obtained thitung > ttabel or 6.151 > 2.042, then H0 is rejected and Ha is accepted.Based on the research that has been done, it can be concluded that learning using the PBL model has a significant effect on the reasoning ability and learning independence of students at MTS Miftahul Hasan.